2011
DOI: 10.1111/j.1365-2796.2011.02378.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aMycobacterium tuberculosis-specific interferon-γ release assay in bronchoalveolar lavage fluid for a rapid diagnosis of tuberculosis

Abstract: Abstract. Jafari C, Kessler P, Sotgiu G, Ernst M,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 26 publications
3
21
0
2
Order By: Relevance
“…Short-term cultures (24 h) have been mainly associated with the detection of a T cell effector memory phenotype, while long-term cultures (5 to 7 days), as used in this study, have been mainly associated with the detection of a T central memory phenotype (25,36,56,57,64). An alternative explanation for the observed reductions in the frequencies of monoand bifunctional CD4 ϩ T cells in peripheral blood samples from PTB patients may involve the previously reported sequestration of CD4 ϩ T cells at the site of infection (65,66). T cell memory generation is critical for specific immune responses.…”
Section: Fig 6 Memory Phenotypes Of Bifunctional Ifn-␥mentioning
confidence: 99%
“…Short-term cultures (24 h) have been mainly associated with the detection of a T cell effector memory phenotype, while long-term cultures (5 to 7 days), as used in this study, have been mainly associated with the detection of a T central memory phenotype (25,36,56,57,64). An alternative explanation for the observed reductions in the frequencies of monoand bifunctional CD4 ϩ T cells in peripheral blood samples from PTB patients may involve the previously reported sequestration of CD4 ϩ T cells at the site of infection (65,66). T cell memory generation is critical for specific immune responses.…”
Section: Fig 6 Memory Phenotypes Of Bifunctional Ifn-␥mentioning
confidence: 99%
“…BAL IGRAs were also assessed in two studies from our own group. In a large European study, JAFARI et al [42] found a negative blood IGRA in 118 out of 250 non-TB patients and 14 (12%) of them had a positive BAL IGRA; in a smaller trial, 40 out of 84 subjects with a confirmed non-TB diagnosis had a negative blood IGRA and six (15%) of them had a positive BAL IGRA [43]. This trial included 10 subjects with a non-tuberculous mycobacterial infection, four of which had a negative blood IGRA, but none had a positive BAL IGRA.…”
Section: Discussionmentioning
confidence: 99%
“…70 % (geringere Sensitivität bei Kindern und HIV-positiven Personen).Wenn die Verdachtsdiagnose der Tuberkulose nicht durch eine mikroskopische Untersuchung und nachfolgende PCR-Untersuchung vorläufig gesichert werden kann, sollte eine Bronchoskopie angestrebt werden. Der diagnostische Zugewinn der mikrobiologischen, molekularbiologischen und histologischen Verfahren zur Diagnose der Lungentuberkulose an bronchoalveolärer Lavage (BAL) und Lungengewebe ist gegenüber den Untersuchungen an Sputum gering[13]. Der Vergleich von systemischen und lokalen M. tuberculosis-spezifischen Immunreaktionen an Zellen aus dem Blut und der BAL im IGRA (T-Spot.TB ® Test, Oxfordimmunotec, Abingdon, UK) erlaubt allerdings eine relativ gute Differenzierung einer latenten Infektion mit M. tuberculosis von einer aktiven Tuberkulose[13].…”
unclassified
“…Der diagnostische Zugewinn der mikrobiologischen, molekularbiologischen und histologischen Verfahren zur Diagnose der Lungentuberkulose an bronchoalveolärer Lavage (BAL) und Lungengewebe ist gegenüber den Untersuchungen an Sputum gering[13]. Der Vergleich von systemischen und lokalen M. tuberculosis-spezifischen Immunreaktionen an Zellen aus dem Blut und der BAL im IGRA (T-Spot.TB ® Test, Oxfordimmunotec, Abingdon, UK) erlaubt allerdings eine relativ gute Differenzierung einer latenten Infektion mit M. tuberculosis von einer aktiven Tuberkulose[13]. Dieses Verfahren eignet sich auch an Pleuraerguss, Liquor cerebrospinalis oder Aszites zur raschen Diagnose einer aktiven Tuberkulose, wenn mikrobiologische und molekularbiologische Methoden nicht wegweisend sind.…”
unclassified